Collaboration in Pediatric Surgical Training & Education among Asian Countries & Beyond Bangladesh perspective (Journal of Paediatric Surgeons of Bangladesh, 2015)
Abstract not availableJ. Paediatr. Surg. Bangladesh 3(2): 54-55, 2012 (July)